The Efforts to Improve Students’ Understanding of Counting Operation Through Picture Card Game at Elementary School - Juraida Juraida (Universitas Tanjungpura, 2021)
The learning process of Mathematics in first grade at SDN 10 Sungai Kakap has tended to be conventional and minimal in using media. In the learning process, students feel bored and did not understand the concept of addition. Therefore, classroom action research was carried out to improve the process and learning outcomes of educators by using picture card games. This study aimed to improve students' understanding of the addition count operation using picture card games. The research subjects were 1 A class students of SDN 10 Sungai Kakap, Kubu Raya Regency, 2018/2019 academic year. Based on the results of classroom action research, it can be concluded that the picture card game can improve the understanding of the addition count operations and the active role of students in learning. It could be seen from the presentation of completeness achieved by students. In the initial data of students who have not completed, it reached 53.33%, after improvements in cycle I the completeness increased to 63.33%. There was improvement in the learning process in cycle II to achieve the success criteria based on the results of reflection in cycle I. Affter completing the test, it increased to 93.33%, and there were still 6.67% of students who had not completed it.